Mobbing in Slovenia: Prevalence, mobbing victim characteristics, and the connection with post-traumatic stress disorder - Mumel , Damijan; Jan, Sanja; Treven, Sonja; Malc, Domen (Naše gospodarstvo/Our economy, 2015)
An increasing number of organizations face the problem of mobbing, which represents a serious, widespread problem with numerous consequences for victims, organizations, and society. We also recognize the connection this phenomenon has with the emergence of post-traumatic stress disorder (PTSD). PTSD poses one of the most critical consequences for victims of mobbing, who mostly consist of employees at lower organizational levels. Our research focuses on the prevalence of mobbing in Slovenia, its correlation to PTSD, and some differences in the subjective and objective assessments of being exposed to mobbing. We found that the prevalence of mobbing in Slovenia can be compared to some previous assessments as well as data from other countries. Among the study’s participants, 24% could be classified as regular victims of mobbing. For the first time, we link mobbing with PTSD using a Slovenian sample. We also recorded some interesting differences between subjective and objective assessments of mobbing, thereby indicating the importance of subjective conceptualizations of mobbing acts, which should be investigated in greater detail in future research.